A Late Dorset semi-subterranean structure from the Bell Site (NiNg-2), Ekalluk River, Victoria Island - Ryan, Karen (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2003)
AbstractThis paper presents a detailed description of the architectural elements associated with a Late Dorset semi-subterranean structure at the Bell site (NiNg-2), located on the Ekalluk River, southeastern Victoria Island, Nunavut. The 2002 excavation of the house centred on the recovery of detailed information relating to the architectural tradition of the Late Dorset in this area. The structural remains associated with House 6 suggest it was intended for only a short period of occupation that corresponded with the late fall caribou migration through the area. Probably abandoned during the early winter, House 6 is best interpreted as a "between seasons" structure, comparable to the Thule and historic Inuit qarmat.